Estimating the tax capacity of goldsmiths versus physicians using the micro approach - Karkon , Amin; Nakhaei, Habibollah; Hajiha , Zohreh (Social Determinants of Health, 2021)
Background: The aim of this study was to Estimating the tax capacity of goldsmiths versus physicians using the micro approach Method: The statistical sample included 384 selected gold dealers and physicians tax declaration since 2013 to 2019 in South Khorasan province. Finally, the main research hypotheses were tested in Eviews and SPSS software using a multivariate regression model using panel data method at a confidence level of 0.95. Results: The results of the present study showed that actual tax revenues were less than tax capacity value in public health area. Also, tax capacity of selected jobs had a significant role on provided services in the statistical population of physicians. There was a significant relationship between the tax capacity of South Khorasan Province and health services; as tax capacity increases, public health services will also increase. There was an inverse and significant relationship between financial revenue effort and emotional and mental performance of South Khorasan province and tax avoidance. Conclusion: Tax avoidance would decrease as financial revenue effort increases and cause the hospital and public health service performance.